2016
DOI: 10.4137/cmc.s36740
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcomes in Pregnant Women with a Prosthetic Mechanical Heart Valve

Abstract: BACKGROUNDPregnancy is associated with several cardiocirculatory changes that can significantly impact underlying cardiac disease. These changes include an increase in cardiac output, sodium, and water retention leading to blood volume expansion, and reductions in systemic vascular resistance and systemic blood pressure. In addition, pregnancy results in a hypercoagulable state that increases the risk of thromboembolic complications.OBJECTIVESThe aim of this study is to assess the maternal and fetal outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
42
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 23 publications
11
42
4
2
Order By: Relevance
“…12 However, there were 3% maternal deaths which is higher with this current study. 12 Shannon et al also reported a maternal mortality rate of 1-4% with prosthetic heart valves who required anticoagulation therapy. 13 But Hagen et al reported that, women with a prosthetic heart valve had 58% chance of experiencing an uncomplicated pregnancy and the maternal mortality rate is 1.4%.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…12 However, there were 3% maternal deaths which is higher with this current study. 12 Shannon et al also reported a maternal mortality rate of 1-4% with prosthetic heart valves who required anticoagulation therapy. 13 But Hagen et al reported that, women with a prosthetic heart valve had 58% chance of experiencing an uncomplicated pregnancy and the maternal mortality rate is 1.4%.…”
Section: Discussioncontrasting
confidence: 65%
“…11 Ayad et al observed that, 15% patients developed heart failure and prosthetic valve thrombosis was in 8%of patients. 12 However, there were 3% maternal deaths which is higher with this current study. 12 Shannon et al also reported a maternal mortality rate of 1-4% with prosthetic heart valves who required anticoagulation therapy.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Warfarin appears to offer the best protection against thromboembolic complications, but the risk of its teratogenic effect is the concern of the clinicians. Some reports indicate that the administration of warfarin is relatively safe during pregnancy if adequate anticoagulation can be achieved at doses of 5 mg or less . Hassouna conducted a systematic review and meta‐analysis to evaluate the merit of warfarin dose not exceeding 5 mg/d; 494 eligible pregnancies reported in 11 studies were included in the meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[22] от-метили ИЭ ИК у одной (1%) женщины, а S. Ayad и соавт. [23] при наблюдении состояния такого же числа беремен-ных -у 2 (2%). Тем не менее отсутствие первичной кла-панной патологии и благополучный анамнез не исключа-ют вероятность инфекционного поражения эндокарда во время беременности [24].…”
Section: эпидемиология и предрасполагающие факторыunclassified